Penerapan Metode Design Thinking pada Model Perancangan UI/UX untuk Aplikasi Daur Minyak - AlAzhari, Muhamad Roihan; Indrawan, Ricky; Soewardikoen, Didit Widiatmoko; Yunidar, Dandi (Politeknik Negeri Batam, 2024)
The Daur Minyak application is designed as a used cooking oil pick-up service, allowing customers to sell their oil, while the service buys and collects it. The app aims to tackle environmental issues caused by improper disposal of used oil. It provides a sustainable solution by enabling users to sell oil that is no longer safe for cooking, in partnership with PT. MBIO. This study focuses on proposing a UI/UX model for the Daur Minyak application using the design thinking method, which includes five stages: Empathize, Define, Ideate, Prototype, and Testing. The prototype was built using Figma and was tested on 12 respondents. Usability was measured with the System Usability Scale (SUS), where the app received a high score of 90, indicating a positive user experience. This design approach aims to create an intuitive and functional app to support efficient used oil management